2021
DOI: 10.1088/1361-6528/abe1ef
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced interfacial reaction of silicon carbide fillers onto the metal substrate in carbon nanotube paste for reliable field electron emitters

Abstract: Adhesion of carbon nanotube (CNT) onto a cathode substrate is very crucial for field electron emitters that are operating under high electric fields. As a supporting precursor of CNT field emitters, we adopted silicon carbide (SiC) nano-particle fillers with Ni particles and then enhanced interfacial reactions onto Kovar-alloy substrates through the optimized wet pulverization process of SiC aggregates for reliable field electron emitters. As-purchased SiC aggregates were efficiently pulverized from 20 to less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In the DIR-CNT paste emitter, the Si 2p 3/2 of the Si–C bond was confirmed at a binding energy of about 100.4 eV, which is generated by the extra reactant SiC nanoparticles. The binding state to the SiO 2 phase was confirmed at a binding energy over 102 eV, which can arise from the surface oxidation of the SiC nanoparticles themselves and the oxidation reaction that may occur during the fabrication process of the emitter . Furthermore, not only a strong Ni 2 Si phase at a binding energy of 99.4 eV but also an additional NiSi phase at a binding energy of 98.5 eV were found in the DIR-CNT paste emitter .…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In the DIR-CNT paste emitter, the Si 2p 3/2 of the Si–C bond was confirmed at a binding energy of about 100.4 eV, which is generated by the extra reactant SiC nanoparticles. The binding state to the SiO 2 phase was confirmed at a binding energy over 102 eV, which can arise from the surface oxidation of the SiC nanoparticles themselves and the oxidation reaction that may occur during the fabrication process of the emitter . Furthermore, not only a strong Ni 2 Si phase at a binding energy of 99.4 eV but also an additional NiSi phase at a binding energy of 98.5 eV were found in the DIR-CNT paste emitter .…”
Section: Resultsmentioning
confidence: 89%
“…23 The adhesion layer made of silicon carbide (SiC) and nickel (Ni) nanoparticles as inorganic fillers functions to improve the adhesion property of the CNT emitters by forming a Ni silicide phase reacted with the Kovar substrates through a post-high-temperature vacuum-annealing process. 24 We demonstrated that the adhesion property of the CNT paste emitter by the adhesion layer contributed to reliable and stable FE characteristics. Meanwhile, because the adhesion layer serves as the electron transport between the CNT emitters and cathode substrates, a study on its band structure needs to be conducted.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations